Tingkat Depresi pada Pasien Diabetes Mellitus Tipe II di Poliklinik Penyakit Dalam - Rahayu Setyowati; Dede Ninah Rahmawati; Aat Agustini; Firman Sugiharto (Universitas Malahayati, 2026)
ABSTRACT Type II Diabetes Mellitus (DM) is a chronic metabolic disorder that affects not only physical health but also patients’ psychological well-being. Depression is one of the most prevalent psychological complications associated with DM, which can worsen glycemic control, reduce treatment adherence, and impair self-care behaviors. Despite its clinical importance, depression among diabetic patients often remains underrecognized, particularly in regional healthcare settings. This study aimed to describe the levels of depression among patients with Type II Diabetes Mellitus at the Internal Medicine Polyclinic of Majalengka Regional Hospital and to analyze its distribution based on age, gender, and duration of illness. A quantitative descriptive design was employed involving 90 respondents selected through convenience sampling who met the inclusion criteria: adults (≥18 years old) diagnosed with Type II DM and willing to participate. Data were collected using the Beck Depression Inventory-II (BDI-II), a validated international instrument with high internal consistency (Cronbach’s Alpha 0.8). Data were analyzed univariately using frequency and percentage distributions to illustrate the levels of depression according to demographic characteristics. Most respondents experienced moderate depression (40%), followed by mild (24.4%) and severe depression (18.9%), while only 16.7% were categorized as normal. Higher levels of depression were observed among female respondents, older adults (60 years), and those who had lived with diabetes for ≤5 years. Depression represents a significant psychological comorbidity among patients with Type II DM, underscoring the need for integrated and routine mental health screening in diabetic care. Implementing holistic interventions based on a bio-psycho-social-spiritual framework is essential to improve emotional well-being, self-management, and overall quality of life among diabetic patients at both primary and hospital-level healthcare settings. Keywords: Type II Diabetes Mellitus, Depression, Beck Depression Inventory-II, Mental Health, Chronic Disease Nursing. ABSTRAK Diabetes Mellitus (DM) tipe II merupakan penyakit metabolik kronis yang tidak hanya berdampak pada kondisi fisik, tetapi juga aspek psikologis pasien. Depresi menjadi salah satu komplikasi psikologis yang paling sering terjadi dan dapat memperburuk kontrol glikemik, menurunkan kepatuhan terhadap pengobatan, serta menghambat proses penyembuhan. Meskipun demikian, gejala depresi pada pasien DM sering kali tidak teridentifikasi secara dini, khususnya di fasilitas kesehatan daerah. Penelitian ini bertujuan untuk menggambarkan tingkat depresi pada pasien Diabetes Mellitus tipe II di Poliklinik Penyakit Dalam RSUD Majalengka, serta menganalisis distribusinya berdasarkan usia, jenis kelamin, dan lama menderita DM. Penelitian ini menggunakan desain deskriptif kuantitatif dengan teknik convenience sampling terhadap 90 responden yang memenuhi kriteria inklusi, yaitu pasien DM tipe II berusia ≥18 tahun dan bersedia berpartisipasi. Pengumpulan data dilakukan menggunakan instrumen Beck Depression Inventory-II (BDI-II) yang memiliki reliabilitas tinggi. Analisis data dilakukan secara univariat dengan distribusi frekuensi dan persentase. Sebagian besar responden mengalami depresi sedang (40%), diikuti oleh depresi ringan (24,4%) dan depresi berat (18,9%), sementara hanya 16,7% yang berada dalam kategori normal. Tingkat depresi lebih tinggi ditemukan pada perempuan, kelompok usia lanjut (60 tahun), dan pasien dengan durasi penyakit ≤5 tahun. Depresi merupakan komorbiditas yang umum terjadi pada pasien DM tipe II dan perlu mendapatkan perhatian klinis yang setara dengan aspek fisik penyakit. Diperlukan skrining psikologis rutin dan intervensi holistik berbasis bio-psiko-sosial-spiritual untuk meningkatkan kesejahteraan emosional dan kualitas hidup pasien diabetes di tingkat pelayanan primer maupun rumah sakit. Kata Kunci: Diabetes Mellitus Tipe II, Depresi, Beck Depression Inventory-II, Kesehatan Mental, Keperawatan Kronis.